2006
DOI: 10.1089/rej.2006.9.77
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Beta Immunotherapy for the Prevention and Treatment of Alzheimer Disease: Lessons from Mice, Monkeys, and Humans

Abstract: Alzheimer disease (AD), the most common form of dementia, is without an effective cure or preventive treatment. Recently, amyloid-beta protein (Abeta) has become a major therapeutic target. Many efforts are underway to either reduce the production of Abeta or enhance its clearance. In 1999, Schenk and colleagues first showed that active immunization with full-length Abeta lowered cerebral Abeta levels in transgenic mice. These findings have been confirmed and extended in various transgenic mouse models of AD u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…A␤-lowering treatments consistently rescue cognitive deficits in many AD transgenic models (4,11,12). More recently, we and others found that paradigms that diminish soluble tau can also ameliorate cognitive decline (13)(14)(15).…”
Section: A␤ and Tau Pathology Are Not Altered By Nsc Transplantationmentioning
confidence: 80%
“…A␤-lowering treatments consistently rescue cognitive deficits in many AD transgenic models (4,11,12). More recently, we and others found that paradigms that diminish soluble tau can also ameliorate cognitive decline (13)(14)(15).…”
Section: A␤ and Tau Pathology Are Not Altered By Nsc Transplantationmentioning
confidence: 80%
“…For the treatment of AD, both passive Aβ immunization (i.e. peripheral administration of anti-Aβ antibodies) and active immunization with Aβ are being explored (1)(2)(3)(4)(5). The amino acid sequence of Aβ 1-42 is 100% conserved between humans and most primates; however, the N-terminal Aβ sequence is not conserved between primates and rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Human APP transgenic mice (PSAPP Tg+, Tg2576, and PDAPP Tg+ mice) exhibit age-dependent changes that are similar to those seen in humans with AD (6)(7)(8)(9). In mouse models of AD, administration of anti-Aβ antibodies or active immunization with Aβ improved cognitive function and reduced amyloid burden (3)(4)(5). Despite numerous preclinical studies with various anti-Aβ antibodies, there is no consensus on their mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Human -amyloid peptide removal/treatment has remarkable effects in ischemic brain injury (Pluta et al, 1998a;Pluta et al, 1999;Pluta, Ulamek 2008) and less effect in mice with overexpressed amyloid pathology (Schenk et al, 1999). Experience in patient's vaccination was less convincing (Nicoll et al, 2003;Lemere et al, 2006;Hawkes, McLaurin 2007). Trials in cases with amyloid pathology were stopped when 6% of immunized patients developed meningoencephalitis (Nicoll et al, 2003;Orgogozo et al, 2003;Gilman et al, 2005).…”
Section: Disabilities After Ischemiamentioning
confidence: 99%